Enhancing Children’s Social Development Through Micro Role-playing Method - Wilda Amalia; Farida Mayar (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to test the micro role-playing method for children's social development in an Islamic Kindergarten in Bukittinggi City. This research uses a quantitative approach with experimental methods, with a research-designed group pretest-posttest. Data collection techniques use observation and data analysis techniques using homogeneity tests, normality tests, and t-tests. The sample for this research was ten young children aged 5-6 years. The results show that from the pre-test. The researchers got (6.7) in the undeveloped category. After doing a pretest, researchers did treatment times with treatment (7.8) categorized as not yet developed, treatment 2 (9.2) categorized as starting to develop, treatment 3 (12.7) believed to be starting to develop, and treatment 4th (19.4) was categorized as developing as expected. The researcher did a post-test with results (19.7) categorized as developing as expected. Comparing the magnitude of t obtained by calculation (t = 43.33) and the magnitude of t listed in the t value table at the 5% significance level, namely 2.26, it is known that t0 is greater than t, namely 43.33 2.26. Because t0 is greater than t1 the value hypothesis (h0) proposed is rejected and the alternative hypothesis is accepted (ha). This means that the micro role-playing method can improve the social development of children in kindergarten.